'After the manner of Jael and Sisera': Transforming Violence and Mental Pain in Charlotte Brontë's Villette. (3rd April 2021) - Franklin, Sophie
Abstract : This article explores the transformation of violence in religiously inflected representations of mental pain in Charlotte Brontë's Villette (1853). Through the appropriation of the Old Testament narrative of Jael and Sisera (Judges 4), Brontë presents vivid, embodied re-enactments of Lucy Snowe's psychological suffering and self-harm. These representations of self-inflicted pain provide a complex picture of literary violence as transformational. In the process of examining such transformation, this article engages with critical debates and shifting perceptions surrounding issues of pain, materialism and faith in the mid-nineteenth century, while also intersecting with ongoing conversations around matters of mental health. Villette narrates mental pain, transforming seemingly invisible experiences of suffering into witnessable and enduring testimonies of survival.